Comparison of Sula Liquid Media and Conventional Method for Diagnosis of MDR-TB - Iqbal, Hasina; Mamun, KZ; Shamsuzzaman, SM; Kamal, SM Mostafa (Journal of Dhaka Medical College, 2017)
Background: Tuberculosis is probably the most important infectious disease of human. Early diagnosis of tuberculosis and initiating prompt treatment has been the mainstay in interrupting the transmission of the infection to others in the community. Aim: The present study was aimed at evaluating and comparing the different media which are available for the diagnosis of tuberculosis and at determining their feasibility as diagnostic tests in terms of their effectiveness and affordability. Methods: 100 Z-N stain positive samples were taken from NIDCH, Mohakhali, Dhaka. All samples were cultured on LJ media for 4-6 wks and sula liquid media for 12 days. Drug sensitivity tests against isoniazid (INH), rifampicin (RIF), streptomycin (SM) and ethambutol (EMB) were done by both conventional (LJ media) and slide method and additional sensitivity were done against second line drugs such as gatifloxacin (G), kanamycin (K) and ofloxacin (OF) only by slide method. Sensitivity test against P-nitro benzoic acid (PNB) were also done to differentiate typical Mycobacterium from atypical Mycobacterium by both slide and conventional methods. Results: Of the 100 sputum samples which were inoculated onto the sula liquid and LJ medium, all showed growth of Mycobacterium tuberculosis on sula liquid media after a mean incubation period of 7 days and on LJ medium after a mean incubation period of 34 days. Conclusion: Sula liquid media had an advantage of a shorter turn around period of 12 days when compared with conventional L-J media. J Dhaka Medical College, Vol. 25, No.2, October, 2016, Page 100-104